The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.17580/or.2021.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Fine hydraulic screening for staged separation of titanium-magnetite concentrate

Abstract: This article covers the applications of fine hydraulic screening for the staged separation of titanium-magnetite concentrates upstream of the last grinding stage and provides an evaluation of its process efficiency options for the Kachkanarsky GOK. In all screen operating modes tested, the mass fraction of iron in the undersize was higher than its mass fraction in the oversize, but failed to reach the target value for the concentrate of 61 %. Therefore, the undersize must be subjected to additional magnetic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…2. The following can be used as beneficiation methods and devices for the staged concentrate separation: drum magnetic-gravity separators with a modified bath [23]; drum separators with an alternating magnetic field [24, 25]; MGS magnetic-gravity separators of a cylindrical type with a vertical direction of movement of the separated products [26]; fine screening [27]; gravity separation (screw separation) [5].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2. The following can be used as beneficiation methods and devices for the staged concentrate separation: drum magnetic-gravity separators with a modified bath [23]; drum separators with an alternating magnetic field [24, 25]; MGS magnetic-gravity separators of a cylindrical type with a vertical direction of movement of the separated products [26]; fine screening [27]; gravity separation (screw separation) [5].…”
mentioning
confidence: 99%
“…Therefore, the most promising for industrial application are practices with staged concentrate separation using a combined circuit with fine screening and magnetic separation of the undersize product (Table 5). The results of industrial tests of the staged concentrate separation using fine screening at the Kachkanarsky GOK showed that this technology makes it possible to reduce the volume of mills at the third stage by 25-33 % or increase the productivity of the beneficiation plant by 10 % [27]. With the same productivity of the plant and the volume of the mills at the third stage, the use of staged extraction of concentrate makes it possible to increase the extraction of iron into concentrate by 0.5-1 %.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The operating principle of MG separation is based on the control of magnetic aggregation when a ferromagnetic suspension is exposed to a low-strength magnetic field and a centrifugally ascending water flow. Fine screening is widely used at many mining and beneficiating enterprises for diverse types of mineral raw materials and makes it possible to achieve an increase in the productivity of beneficiating plants, improve the quality of products, and reduce operating costs [25][26][27][28][29][30][31].…”
mentioning
confidence: 99%